STUDENTS’ HABIT OF WATCHING ENGLISH MOVIES IN ACQUIRING VOCABULARY - Mentari Sukma Yanti; Andi Rachmawati Syarif; Tri Indah Rusli (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The study explores the impact of English movies on students' vocabulary acquisition in Indonesia, focusing on how students acquire vocabulary through their habits of watching English movies. Using a descriptive qualitative approach, the research analyses the relationship between movies and English language learning. The findings reveal that regular watching English movie improved vocabulary, particularly difficult words. Participants felt more confident using new vocabulary in daily conversations and understood the meaning of words contextually. Additionally, this study identifies several key themes that contribute to vocabulary acquisition: input experience and understanding, the influence of subtitles, challenges and strategies in understanding dialogue, visuals as learning support, reflection and learning experience, and the impact of the habit of watching movies. The findings support Krashen’s Input Hypothesis theory, suggesting that movies can be used as an effective learning tool to expand vocabulary. However, the study has limitations, such as its limited sample size and the focus on one movie genre. Future research should involve more diverse participants, explore different movie genres, and use mixed methods to obtain more comprehensive data.